Essay: En temperaturmåling på erhvervspsykologisk coaching lige nu - Kjerulf, Stig (Coaching Psykologi - The Danish Journal of Coaching Psychology, 2012)
Stig Kjerulf Kjerulf & Partnere A/S Sauntesvej 13 2820 Gentofte E-mail: info@kpas.dk